Indigenous Dayak Iban customary perspective on sustainable forest management, West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Leo S, Supriatna J, Mizuno K, Margules C. 2021. Indigenous Dayak Iban customary perspective on sustainable forest management, West Kalimantan, Indonesia. Biodiversitas 23: 424-435. Borneo is the third-largest island in the world, is rich in biodiversity and has diverse unique ecosystems. However, deforestation and land tenure conflicts continue to threaten the indigenous people who rely on forest resources for their livelihoods and well-being. This study aimed to identify the ecosystem services and the value of customary forest resources, identify local wildlife species, and document the traditional knowledge that the Iban indigenous community of West Kalimantan use to manage their customary forest. We collected relevant data using Toolkit for Ecosystem Service Site-based Assessment (TESSA), in-depth interviews, and wildlife surveys. The customary forest provides significant ecosystem services, mainly carbon sequestration (exceeds US$ 52 million/year), water-related services (exceeds US$ 21 million/year), and the 52 wildlife species recorded in the customary forest. Forest resources are managed successfully by the community through traditional knowledge and customary laws passed down for generations. The integration of local and expert knowledge and involvement from all related stakeholders would boost sustainable forest management and enhance the economic benefits and livelihoods of the community. Following current trends, recognizing customary forest and appropriate sustainable forest management could effectively tackle deforestation and land tenure conflicts in Borneo. Further studies should be considered to develop specific activities on managing the forest sustainably that the community can implement and evaluate.
Keywords: Dayak Iban, deforestation, ecosystem service, sustainable forest management, traditional knowledge